2020
DOI: 10.1590/1807-7692bar2020190031
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue at Work: Scale Validation with Airline Pilots

Abstract: In the organizational context, the study of occupational stress encompasses constructs of fatigue at work. Within the air transportation sector, fatigue at work is a potential issue influencing both safety and occupational stress. The objective of the present study was to perform a convergentdiscriminant validity analysis of the Feeling of Fatigue scale in the area of Administration. Data from an observational cross-sectional study involving a sample of 1,066 airline pilots were analyzed using quantitative mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
0
2
0
1
Order By: Relevance
“…One of them (i.e., validity evidence based on the relations to other variables) was only analyzed from a correlational perspective with five related constructs. Further research on the BAT's scores' relations to other variables should expand to other conceptually linked constructs such as fatigue using, for example, the Portuguese adaptation of the Occupational Fatigue Exhaustion/Recovery [6] or the Brazilian adaptation of the Feeling of Fatigue scale [123]. Test-criterion relationships should be analyzed in future studies using a predictive or concurrent design.…”
Section: Weaknesses Strengths and Suggestions For Further Researchmentioning
confidence: 99%
“…One of them (i.e., validity evidence based on the relations to other variables) was only analyzed from a correlational perspective with five related constructs. Further research on the BAT's scores' relations to other variables should expand to other conceptually linked constructs such as fatigue using, for example, the Portuguese adaptation of the Occupational Fatigue Exhaustion/Recovery [6] or the Brazilian adaptation of the Feeling of Fatigue scale [123]. Test-criterion relationships should be analyzed in future studies using a predictive or concurrent design.…”
Section: Weaknesses Strengths and Suggestions For Further Researchmentioning
confidence: 99%
“…Then, 32 questions were included in four dimensions: work status ( 51 53 ), workload ( 50 ), work schedule ( 54 , 55 ) and working conditions ( 56 , 57 ). Finally, the questionnaire was subjected to reliability and validity tests ( 58 , 59 ), as well as an EFA and validation factor analysis ( 60 , 61 ). The results showed that the alpha coefficient of the pilot survey data tested the reliability of the questionnaire, and the KMO value and Bartlett's spherical test were used to test the correlation of the questionnaire's question variables, which showed that the questionnaire had good validity and that the survey data were correlated and suitable for a factor analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Para avaliar a fadiga no trabalho são desenvolvidos instrumentos psicométricos de medida (Celestino, Bucher-Maluschke, & Marqueze, 2020;Frone & Blais, 2020b;Frone & Tidwell, 2016). No contexto brasileiro, alguns instrumentos possuem tradição de uso em pesquisas, sendo eles: a) Piper Fatigue Scale (Mota, Pimenta, & Piper, 2009), b) Escala de avaliação da fadiga (De Vries, Michielsen, Van Heck, & Drent, 2004;Gouveia et al, 2015); c) Chalder Fatigue Questionnaire (Cho et al, 2007) e; d) The Need for Recovery Scale (NFR) (Moriguchi et al, 2012).…”
Section: Introductionunclassified